Criopreservação e sementes sintéticas de jenipapeiro - Nascimento, Cyntia Maia do (2018)
Currently, the preservation of native genetic resources in Brazil has become a priority in several research institutions. Among the native species in the Northeast region of Brazil, the fruit tree Genipa americana L. is considered highly promising for immediate use. The conservation of the genetic resources of this perennial crop, exploited by predatory forest extractivism, is mainly based on field collections. Seed collection and storage is hampered by the physiology, since the seed performance during storage is intermediary, particularly for being intolerant to extremely low desiccation levels. In this sense, the application of cryopreservation techniques, which includes the conservation of plant material at ultra low temperature by immersion in liquid nitrogen at -196ºC, paralyzes all activities, such as cell division and metabolic reactions, allowing the storage of plant material for an indeterminate period. The application of the synthetic or artificial seed technique is a complementary strategy for the conservation of the existing genetic variability, and acceleration of the propagation of superior genotypes. The objective of this study was to deepen the technicalscientific knowledge about the conservation of embryonic axes of genipap by means of cryopreservation and to study the nutritional aspects of the encapsulation matrix of synthetic seeds derived from shoot tips.